Synthesis of enantiopure 1, 2-azido and 1, 2-amino alcohols via regio- and stereoselective ring-opening of enantiopure epoxides by sodium azide in hot water. Issue 2 (15th February 2016) - Wang, Hai-Yang; Huang, Kun; De Jesús, Melvin; Espinosa, Sandraliz; Piñero-Santiago, Luis E.; Barnes, Charles L.; Ortiz-Marciales, Margarita
Graphical abstract: Abstract: A practical and convenient method for the efficient and regio- and stereoselective ring-opening of enantiopure monosubstituted epoxides by sodium azide under hydrolytic conditions is reported. The ring-opening of enantiopure styryl and pyridyl ( S )-epoxides by N3 − in hot water takes place preferentially at the internal position with complete inversion of configuration to produce ( R )-2-azido ethanols with up to 99% enantio- and regioselectivity, while the ( S )-adamantyl oxirane provides mainly the ( S )-1-adamantyl-2-azido ethanol in excellent yield. In general, 1, 2-amino ethanols were obtained in high yield and excellent enantiopurity by the reduction of the chiral 1, 2-azido ethanols with PPh3 in water/THF, and then converted into the Boc or acetamide derivatives. Abstract : ( R )-2-Azido-2-phenylethanol: C8 H9 N3 O ee = 99% [ α ]D 22 = −268 ( c 0.7, CHCl3 ) Source of chirality: Asymmetric synthesis Absolute configuration: ( R ) Abstract : ( R ) Azido-2-(4-chlorophenyl)ethanol: C8 H8 N3 OCl ee = 98% [ α ]D 22 = −151 ( c 1.0, CHCl3 ) Source of chirality: Asymmetric synthesis Absolute configuration: ( R ) Abstract : ( R )-2-Azido-2-(4-nitrophenyl)ethanol: C8 H8 N4 O3 ee = 73% [ α ]D 22 = −111 ( c 0.6, CHCl3 ) Source of chirality: Asymmetric synthesis Absolute configuration: ( R ) Abstract : ( S )-2-Azido-1-(4-nitrophenyl)ethanol: C8 H8 N4 O3 ee = 90% [ α ]D 22 = +76 ( c 0.22, CHCl3 ) Source of chirality: Asymmetric synthesis Absolute configuration: ( S ) Abstract : ( R )-2-Azido-2-(4-bromophenyl)ethanol: C8 H8 BrN3 ee = 97% [ α ]D 22 = −373 ( c 0.15, CHCl3 ) Source of chirality: Asymmetric synthesis Absolute configuration: ( R ) Abstract : ( R )-2-Azido-2-(3-bromophenyl)ethanol: C8 H8 BrN3 O ee = 99% [ α ]D 22 = −174 ( c 0.4, CHCl3 ) Source of chirality: Asymmetric synthesis Absolute configuration: ( R ) Abstract : ( R )-2-Azido-2-( p -tolyl)ethanol: C9 H11 N3 O ee = 95% [ α ]D 22 = −190 ( c 0.3, CHCl3 ) Source of chirality: Asymmetric synthesis Absolute configuration: ( R ) Abstract : ( R )-2-Azido-2-(3-methoxyphenyl)ethanol: C9 H11 N3 O2 ee = 99% [ α ]D 22 = −200 ( c 0.6, CHCl3 ) Source of chirality: Asymmetric synthesis Absolute configuration: ( R ) Abstract : ( R )-2-Azido-2-(4-fluorophenyl)ethanol: C8 H8 FN3 O ee = 99% [ α ]D 22 = −182 ( c 0.8, CHCl3 ) Source of chirality: Asymmetric synthesis Absolute configuration: ( R ) Abstract : ( R )-2-Azido-2-(4-methoxyphenyl)ethanol: C9 H11 N3 O2 ee = 98% [ α ]D 22 = −148 ( c 2, MeOH) Source of chirality: Asymmetric synthesis Absolute configuration: ( R ) Abstract : ( R )-2-Azido-2-(3-pyridyl)ethanol: C7 H8 N4 O ee = 95% [ α ]D 22 = −194 ( c 3.2, CHCl3 ) Source of chirality: Asymmetric synthesis Absolute configuration: ( R ) Abstract : ( S )-1-(Adamantan-1-yl)-2-azidoethan-1-ol: C12 H19 N3 O ee = 99.5% [ α ]D 20 = −18 ( c 1.1, MeOH) Source of chirality: Asymmetric synthesis Absolute configuration: ( S ) Abstract : ( R )-2-Amino-2-phenylethanol: C8 H11 NO ee = 99% [ α ]D 22 = −62 ( c 0.2, CHCl3 ) Source of chirality: Asymmetric synthesis Absolute configuration: ( R ) Abstract : ( R )-Amino-2-(4-chlorophenyl)ethanol: C8 H10 ClNO ee = 99% [ α ]D 22 = −68 ( c 0.2, CHCl3 ) Source of chirality: Asymmetric synthesis Absolute configuration: ( R ) Abstract : ( R )-2-Amino-2-(4-bromophenyl)ethanol: C8 H10 BrNO ee = 99% [ α ]D 22 = −62 ( c 0.15, CHCl3 ) Source of chirality: Asymmetric synthesis Absolute configuration: ( R ) Abstract : ( R )-2-Amino-2-(3-bromophenyl)ethanol: C8 H10 BrNO ee = 99% [ α ]D 22 = −51 ( c 0.6, CHCl3 ) Source of chirality: Asymmetric synthesis Absolute configuration: ( R ) Abstract : ( R )-2-Amino-2-( p -tolyl)ethanol: C9 H13 NO ee = 99% [ α ]D 22 = −50 ( c 0.09, CHCl3 ) Source of chirality: Asymmetric synthesis Absolute configuration: ( R ) Abstract : ( R )-2-Amino-2-(3-methoxyphenyl)ethanol: C9 H13 NO2 ee = 99% [ α ]D 22 = −39 ( c 0.09, CHCl3 ) Source of chirality: Asymmetric synthesis Absolute configuration: ( R ) Abstract : ( R )-2-Amino-2-(4-fluorophenyl)ethanol: C8 H10 FNO ee = 99% [ α ]D 22 = −58 ( c 0.3, CHCl3 ) Source of chirality: Asymmetric synthesis Absolute configuration: ( R ) Abstract : ( R )-2-Amino-2-(4-methoxyphenyl)ethanol: C9 H13 NO2 ee = 99% [ α ]D 18 = +38 ( c 0.43, CHCl3 ) Source of chirality: Asymmetric synthesis Absolute configuration: ( R ) Abstract : ( R )-2-Amino-2-(3-pyridyl)ethanol: C7 H10 N2 O ee = 95% [ α ]D 20 = −40 ( c 1.0, CHCl3 ) Source of chirality: Asymmetric synthesis Absolute configuration: ( R ) Abstract : ( S )-1-(Adamantan-1-yl)-2-aminoethan-1-ol: C12 H21 NO ee = 96% [ α ]D 20 = +19 ( c 1.1, MeOH) Source of chirality: Asymmetric synthesis Absolute configuration: ( S )